Day Ward Glaucoma Patients Have Lower Depression Levels and Higher Glaucoma Knowledge Levels than Inpatients. (8th September 2019) - Xiao, Huiming; Huang, Wenmin; Qin, Xi; Zuo, Chengguo; Yang, Qiongman; Li, Rong; Lin, Mingkai
Abstract : Importance . Psychological factors and glaucoma knowledge are closely related to the effects of glaucoma treatment. Background . Studies comparing anxiety and depression levels and glaucoma knowledge between glaucoma day-case patients and inpatients are limited. Design . Randomized clinical trial. Participants . Consecutive patients undergoing surgery were prospectively enrolled. Methods . Patients were randomized into the day-case group or the inpatient group. All of the patients underwent corresponding procedures for treatment, care, and education. All participants were asked to complete the General Condition Questionnaire, the Hospital Anxiety and Depression Scale (HADS), and the Gray Glaucoma Knowledge Questionnaire (GGKQ) at admission and the HADS and GGKQ at discharge. Main Outcome Measures . The scores for the General Condition Questionnaire, the HADS, and the GGKQ. Results . In total, 216 patients were enrolled in this study, including 119 day ward patients and 97 inpatients. There were no significant differences between the two groups in terms of their baseline demographic and clinical data (P > 0.05 ). The baseline HADS-anxiety (HADS-A), HADS-depression (HADS-D), and GGKQ scores were similar in both groups (P > 0.05 ). Before discharge, the difference in HADS-A scores between the two groups was not significant; however, the HADS-D scores of the day-case inpatients were significantly lower ( α = 0.05, P < 0.001 ), and the GGKQ scores of day-case inpatients were significantly higher than those of the inpatients before discharge ( α = 0.05, P < 0.001 ). Conclusions and Relevance . Day ward patients had lower levels of depression and higher levels of glaucoma knowledge.